2012
DOI: 10.1007/s11418-012-0726-z
|View full text |Cite
|
Sign up to set email alerts
|

Antihyperalgesic activity of chlorogenic acid in experimental neuropathic pain

Abstract: Chlorogenic acid (CGA) is a natural organic phenolic compound that is found in many plants, fruits and vegetables. CGA has beneficial bioactivities and strong therapeutic effects in inflammatory processes. CGA-rich fractions have analgesic activity but CGA has not been tested previously in neuropathic pain, which results from tissue damage, inflammation or injury of the nervous system. Chronic constrictive nerve injury (CCI) is a peripheral neuropathic pain model which initiates an inflammatory cascade. We aim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 31 publications
1
37
0
Order By: Relevance
“…16,39) CGA, a natural phenolic compound found in human diet, has been reported to exhibit potent antioxidant and antiinflammatory activities. [18][19][20][21]40) Hypoglycemic effects of CGA has been shown in diabetic rats. 23,41) CGA may have particularly beneficial effects on healing as a result of its properties.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…16,39) CGA, a natural phenolic compound found in human diet, has been reported to exhibit potent antioxidant and antiinflammatory activities. [18][19][20][21]40) Hypoglycemic effects of CGA has been shown in diabetic rats. 23,41) CGA may have particularly beneficial effects on healing as a result of its properties.…”
Section: Discussionmentioning
confidence: 99%
“…CGA was administered at a dose of 100 mg/kg, and PBS, which was used as a vehicle to dissolve CGA, was administered to the control groups. The dosage of CGA was selected from the effective dose of our previous study 20) and from preliminary experiments for this study (data not shown). The CGA and PBS treatments were started after operation on the surgery day and continued for postoperative six days.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The antioxidant, anti-inflammatory, radioprotective, antiulcerogenic, and analgesic effects of CGA have been well described (Bagdas et al 2013;Cinkilic et al 2013;Dos Santos et al 2006;Shimoyama et al 2013;Yun et al 2012). Experimentally, CGA has also been reported to have free radical scavenging and antagonistic effects against lipid peroxidation in different organs (Oboh et al 2013;Shimoyama et al 2013;Yun et al 2012).…”
Section: Introductionmentioning
confidence: 96%